1557 The development of sleep and safety decision making among less experienced/'young' truck drivers: a qualitative descriptive study. (24th April 2018) - Heaton, Karen; Mumbower, Rachael; Childs, Gwendolyn
Abstract : American truck drivers are at risk for sleep deprivation and subsequent increased risk for sleep – related motor vehicle crash. In spite of their significant risks, little is known about how truck drivers make sleep and safety decisions. The purpose of this study was to describe influences on sleep and safety-related decision-making among a group of long-haul truck drivers. The qualitative descriptive study focused on a purposive sample (n=10) recruited from truckstops, by word of mouth, and flyers posted at locations commonly visited by truck drivers. Semi-structured interviews were conducted with participants. All interviews were audio-recorded and transcribed verbatim prior to analysis. A cyclic approach to coding was used to develop and revise the code book. The process was repeated until themes were generated. Trustworthiness and credibility were enhanced by using reflexivity, an audit trail, and interpretive convergence. Four general themes emerged from driver descriptions of influences of health-related decision making: individual driver characteristics key events, relationships with others, and company–level factors. From analysis of the interviews, it was clear that individual driver characteristics, key events, personal and professional relationships, and company-level factors all influenced health and safety decision-making of this sample of long-haul truck drivers. An important finding was that drivers new to the profession ('young drivers') evolved over time as they gained experience to self-advocate for their sleep and safety – related health needs; and thus, made different sleep decisions. Factors influencing health and safety decision-making must be considered when providing care and teaching to truck drivers. Involving family members and important others to assist in motivating truck drivers may be an effective strategy to positively influence health and safety decision-making. It will be especially important to target interventions to the less experienced ('younger') drivers. Findings from this study may be used to inform the development of educational materials and other interventions to positively influence truck driver health and safety decision-making, which could lead to a healthier transportation workforce and safer highways for the public.